2020
DOI: 10.3390/en13071564
|View full text |Cite
|
Sign up to set email alerts
|

Performance Study on Methanol Steam Reforming Rib Micro-Reactor with Waste Heat Recovery

Abstract: Automobile exhaust heat recovery is considered to be an effective means to enhance fuel utilization. The catalytic production of hydrogen by methanol steam reforming is an attractive option for onboard mobile applications, due to its many advantages. However, the reformers of conventional packed bed type suffer from axial temperature gradients and cold spots resulting from severe limitations of mass and heat transfer. These disadvantages limit reformers to a low efficiency of catalyst utilization. A novel rib … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…It has been proved by many related studies that the performance of the catalyst is largely determined by the phase composition, microstructure and surface morphology of the bimetallic or multimetallic catalyst [199][200][201]. The coordination of electron configuration and geometry among metal components and the effective coordination can make the bimetal or polymetal composites with stronger catalytic capacity [202][203][204][205]. In order to highlight the advantages of noble metals and non-precious metals, we reviewed the bimetallic or polymetallic composite catalysts formed by noble metals and non-precious metals.…”
Section: Direction Of Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proved by many related studies that the performance of the catalyst is largely determined by the phase composition, microstructure and surface morphology of the bimetallic or multimetallic catalyst [199][200][201]. The coordination of electron configuration and geometry among metal components and the effective coordination can make the bimetal or polymetal composites with stronger catalytic capacity [202][203][204][205]. In order to highlight the advantages of noble metals and non-precious metals, we reviewed the bimetallic or polymetallic composite catalysts formed by noble metals and non-precious metals.…”
Section: Direction Of Developmentmentioning
confidence: 99%
“…and the rate determining step is: Wang et al studied a MSR rib microreactor heated by automobile exhaust [205]. The effect of the inlet exhaust and methanol-to-steam ratio on the performance of the reactor were numerically analyzed with a computational fluid dynamic study.…”
Section: Unconventional Reactor Configuration Simulation and Theoreti...mentioning
confidence: 99%
“…However, this kind of reactor requires high temperature, which is its disadvantage, so other reactors have been studied in recent years, such as membrane reactors [56,57] and microporous reactors [58,59]. Moreover, in recent years, many researchers have made great efforts in the design of methanol reforming reactors and have achieved good results; for example, Mironova et al designed a flow reactor with a Pd-Cu membrane in which methanol steam reforming can achieve a high hydrogen yield compared to conventional reactors [60], while Wang et al designed a rib-type microreactor for methanol steam reforming and found that the conversion rate of methanol reached 99.4% [59]. With the development of science and technology, 3D printing technology is also used to design catalysts [61]; this technology can design a reactor suitable for catalysts.…”
Section: Introductionmentioning
confidence: 99%